Autoimmune pulmonary alveolar proteinosis with features similar to nonspecific interstitial pneumonia. (2022) - Fujii, Koki; Takeshima, Hideyuki; Nishimura, Taku; Sakatani, Toshio; Masuda, Yoshio; Morikawa, Teppei; Usui, Kazuhiro
Abstract: A 58-year-old woman with cough and dyspnea who was suspected of having idiopathic interstitial pneumonia had been treated with corticosteroids and cyclosporine, but the symptoms had worsened. There were no findings to suspect pulmonary alveolar proteinosis (PAP) in the bronchoalveolar lavage fluid, 17 months after the start of treatment. The transbronchial lung biopsy specimens showed eosinophilic bodies that strongly stained with periodic acid-Schiff staining. Anti-granulocyte macrophage colony-stimulating factor (anti-GM-CSF) antibodies were detected in her serum. We diagnosed the patient with autoimmune PAP. Thus, we present a rare case of PAP presenting atypical radiological images and bronchoalveolar lavage fluid findings. Highlights: PAP is characterized by an abnormal accumulation of surfactants in the alveoli. We present a rare case of autoimmune PAP with atypical radiological abnormalities. We present a rare case of autoimmune PAP with atypical BALF findings. It is important to include PAP in the differential diagnosis, even in atypical cases.